Authigenic realgar and gold in dynamic redox gradients developed on historic mine wastes, New Zealand. (October 2018) - Kerr, Gemma; Craw, Dave; Trumm, Dave; Pope, James
Abstract: Complex redox and pH microenvironments have developed on arsenic-rich (percent level As) mine wastes at two gold mine processing areas in southern New Zealand that were abandoned 70–80 years ago. Redox conditions range from surficial zones that are being actively oxidised, with formation of authigenic scorodite and Fe oxides, to zones of active chemical reduction around organic debris where authigenic As sulfides, mainly realgar, are actively forming. Authigenic realgar is forming in low-redox microenvironments in a high-sulfur setting with decomposing primary pyrite and arsenopyrite, and in low-sulfur pre-oxidised As-rich mine tailings. Realgar has formed in close proximity (micron scale) to authigenic and/or detrital arsenolite at one low-sulfur site, and in close proximity (cm scale) to authigenic scorodite at the sulfur-rich site. The latter site also has minor accumulations of authigenic gold, which is nanoparticulate and microparticulate and dispersed through a coating of Fe oxyhydroxide and biofilm on authigenic scorodite. Gold was probably mobilised by ephemeral metastable thiosulfate complexes during oxidation of primary auriferous sulfides, and redeposited as those complexes decomposed. Detrital gold has not been noticeably dissolved and redeposited in the low-sulfur mine wastes. The dynamic redox gradients that have developed on these mine wastes are distinctly different from those that form on most mine wastes elsewhere, where an oxidation front progressively penetrates into primary sulfide residues. The dynamic redox gradients can persist at these New Zealand sites until all the organic debris has decomposed, after which the more reduced components including authigenic realgar will become oxidised. Graphical abstract: Highlights: Dynamic micro-redox zones are forming on arsenic-rich mine wastes Active reduction is occurring around organic debris at base of the redox profiles Authigenic realgar (AsS) is forming on reduced organic debris Authigenic arsenolite (As III 2 O3 ) occurs in close association with some realgar Authigenic gold has precipitated with authigenic scorodite (FeAs V O4 .2H2 O)